Pembuatan Balsem Aromaterapi dari Minyak Atsiri Sereh Wangi (Cymbopogonnardus L. Rendle) - Sylvi, Sylvi; Nelza, Novia; Purba, Switamy Angnitha (NUCLEUS, 2023)
Essential oils are volatile oils or oil fly that is generally tangible fluid obtained from the plant roots, bark, stems, and leaves by steam distillation of water. Plants containing essential oils and has the potential to be developed is a plant citronella (Cymbopogon nardus L. Rendle). The purpose of this study to make products balm aromatherapy essential oils of citronella and test the quality of quality of the aromatherapy balm with water vapor distillation method. The collection of data obtained from the analysis is the analysis parameter identification of compounds, numbers ester, test Total Plate Count, testing Pb method of AAS, the, determination of the refractive index, the determination viksositas, determination of pH balm, and a test of endurance balm, saponification, test molds, metal test Cu and specific gramavity test, and analysis of quality parameters of essential oil (yield and organoleptic tests). Results of analysis of parameter numbers ester (17.6177; 17.7824; 18.5295), test Total Plate Count (0; 3 × 102 and 3 × 102), Pb metal test methods AAS (0.02895; 0.0145; 0.01445), the identification of compounds (+), 1.4675 refractive index, viksositas 439,89cp, 436,01cp, 419,57cp, pH 6 balm, balm endurance test, saponification 11:04; 16.66; 16.76, mold testing namely (-), Cu metal test 0.1743; 0.5242; 0.0222, testing the specific gramavity is 0898; 0.922; 0901. The result of the isolation of essential oils of citronella 27,000 gramam sample was obtained ± 62 mL with the results of citronella essential oil yield of 0.23% v / b; the identification of essential oils generally exhibit containing citronella essential oil.